A very brief guide on how to read a report of an orthodontic clinical trial. (2nd April 2023) - O'Brien, Kevin; Fleming, Padhraig S
Abstract : Clinical trials are the accepted benchmark in the assessment of comparative effectiveness of clinical interventions. They should represent a 'fair test', being less exposed to the effects of bias and confounding, which risk blurring the effects of an intervention or, indeed, in prompting misleading inferences. In this short article, we summarize some of the key considerations to assist with the appraisal of clinical trial reports. In particular, we focus on aspects relating both to the conduct and reporting of orthodontic clinical trials. CPD/Clinical Relevance: Clinical trials are pivotal in informing evidence-based practice. We highlight key features that should be considered in relation to the interpretation of orthodontic trial reports.